Shock alloying of metals by cumulative plasma streams - Ivanov, L.I.; Dedyurin, A.I.; Borovitskaya, I.V.; Krokhin, O.N.; Nikulin, V.Ya.; Peregudova, E.N.; Polukhin, S.N.; Tikhomirov, A.A.; Avraamov, Yu.S.; Shlyapin, A.D. (Вопросы атомной науки и техники, 2006)
The report presents the investigation of a possibility of an application of pulse concentrated energy fluxes for the creation by shock alloying method of pseudo-solid solutions of metals, which interact chemically with each other neither in solid nor in liquid states. As an example of such compounds a system W-Cu was chosen. The experiments were conducted by use of plasma focus facility PF-4 (Installation "TYULPAN") in Lebedev Physical Institute. In the work it was found that the copper plate was welded with the high degree of adhesion to tungsten. The nature of the penetration of chemically neutral atoms of Cu in material of a target (W) is connected probably with two processes – the energy transfer to atoms from concentrated pulse fluxes of energy and the initiation of shock waves and their propagation in the target material.